2021
DOI: 10.18502/jder.5639
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 and Dealing with it: Lessons Learned in a Pre-Hospital Emergency System of Yazd

Abstract: The article's abstract is not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In Tehran, EMS established a coronavirus monitoring committee, expanded the number of employees to properly respond to the increase in the number of patients, and initiated formal staff training to be able to adequately care for patients ( 7 , 13 ). Iran's EMS Organization as one of the agile organizations of the Ministry of Health, Treatment and Medical Education and also as the first line of this system, has used all its power and capacity to provide valuable measures in the management of COVID-19 disease ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Tehran, EMS established a coronavirus monitoring committee, expanded the number of employees to properly respond to the increase in the number of patients, and initiated formal staff training to be able to adequately care for patients ( 7 , 13 ). Iran's EMS Organization as one of the agile organizations of the Ministry of Health, Treatment and Medical Education and also as the first line of this system, has used all its power and capacity to provide valuable measures in the management of COVID-19 disease ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Iran, Afzali et al investigated the lessons acquired in a pre-hospital emergency system in Yazd during the COVID-19 pandemic, they concluded that organizations can use the lessons learnt from COVID-19 management to better examine their performance, methodically record and analyze concerns and challenges and deal with procedures to avoid future performance risks ( 15 ). Researchers in Canada investigated the impact of COVID-19 on emergency medical service call volumes and patient acuity and discovered that the virus may have caused actual changes in emergency medical service demand, which will be of interest to other services preparing for future pandemics or COVID-19 waves ( 16 ).…”
Section: Introductionmentioning
confidence: 99%